(untitled) (Medicine Today, 2017)
Bangladesh is a developing country where maternal death due to obstetric haemorrhage is very high. This study was carried out at Dhaka medical college hospital from January 2013 to December 2013. The aim of this study was to identify the different life threatening complications due to obstetric haemorrhage and also to identify the major causes of maternal death due to obstetric haemorrhage. From total 8500 obstetric admissions during 2013, 597 cases were of obstetric haemorrhage, giving the incidence of 7.02%. PPH was the most common cause of maternal death (75%). Those who survived among them (49.50%) women had PPH. The women who experienced several severe morbidities were in the age group between 20-24year (61.38%). Those who died their age group was 25-29 years (39.28%). Both in morbid cases and death cases most of the women belonged to lower middle class (62.37% and 60.71%). In both groups those who had life threatening complications and those who died most of them came from sub urban area (52.47% and 53.57%). About 42.85% in morbid cases had no regular antenatal check up and those who died among them 42.85% patient also did not take any antenatal checkup . 67.85 % of the death cases had circulatory failure and 59.40% of the severely morbid women also had circulating failure . Next to circulatory failure other morbidities were pulmonary edema ( 29.70%), septicemia ( 4.95%) & DIC (1.98%). Hence the result of the study clearly indicated that low socioeconomic states, irregular antenatal cheek up influence the outcome of obstetric hemorrhage. All death from obstetric hemorrhage are not preventable but regular antenatal check up by well trained health personals can recognize the high risk group or any complications at an early stage and appropriate measures can be taken. Medicine Today 2016 Vol.28(1): 9-11